2013
DOI: 10.1111/jgh.12109
|View full text |Cite
|
Sign up to set email alerts
|

Distinct quasispecies characteristics and positive selection within precore/core gene in hepatitis B virus HBV associated acute‐on‐chronic liver failure

Abstract: The ACLF patients showed distinct quasispecies characteristics with higher complexity and diversity within the HBV precore/core gene. The increased HBV quasispecies complexity and diversity, together with a distinct set of positive selection sites, is likely associated with the development of ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It was suspected that these mutations may contribute to the development of LF (1,(6)(7)(8). However, most of these results were based on in vitro transfection of single HBV replication-competent plasmids with such mutations.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It was suspected that these mutations may contribute to the development of LF (1,(6)(7)(8). However, most of these results were based on in vitro transfection of single HBV replication-competent plasmids with such mutations.…”
Section: Discussionmentioning
confidence: 95%
“…It has been previously reported that coinfection with human immunodeficiency virus (HIV) and HBV results in low quasispecies complexity (4). In patients with HBV infection-related liver failure (HB-LF), the quasispecies showed distinct characteristics with higher complexity and diversity within the HBV precore (preC)/core gene (6). However, there is no clear experimental evidence for a significant role of HBV quasispecies in the pathogenesis of HB-LF.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…By contrast, line probe assays can detect specific variants occurring in > 5% of viral quasispecies [38,39] . Other highly sensitive methods include restriction fragment length polymorphism analysis [40] , clone-based sequencing [41] , and real-time PCR. More recently, several next-generation sequencing methods have been developed, including ultra-deep pyrosequencing, which can detect thousands of clonally amplified regions [42][43][44][45] .…”
mentioning
confidence: 99%